Development of Learning Activities for Solving Physics Problems by Applying Rojas’ Concept of Rectilinear Motion for Grade-10 Students - Chaichana, Kamonchanok; Prachanban, Pakorn (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 3 (2561): July-September 2018, 2018)
การวิจัยมีจุดมุ่งหมายเพื่อ 1) สร้าง ตรวจสอบคุณภาพและหาดัชนีประสิทธิผลของกิจกรรมการแก้โจทย์ปัญหาฟิสิกส์โดยประยุกต์แนวคิดของโรจาส์ 2) เพื่อเปรียบเทียบผลสัมฤทธิ์ทางการเรียนและความสามารถในการแก้โจทย์ปัญหาระหว่างก่อนเรียนและหลังเรียน และศึกษาความสามารถการแก้โจทย์ปัญหาในเชิงคุณภาพ กลุ่มตัวอย่าง คือ นักเรียนชั้นมัธยมศึกษาปีที่ 4 โรงเรียนสุโขทัยวิทยาคม จำนวน 39 คน ที่ได้จากวิธีการสุ่มแบบกลุ่ม เครื่องมือที่ใช้ ได้แก่ แผนการจัดกิจกรรมการแก้โจทย์ปัญหาฟิสิกส์โดยประยุกต์แนวคิดของโรจาส์ แบบทดสอบวัดผลสัมฤทธิ์ทางการเรียน แบบวัดความสามารถการแก้โจทย์ปัญหา และแบบสังเกตพฤติกรรมการแก้โจทย์ปัญหา วิเคราะห์ข้อมูลโดยใช้สถิติ t-test for Dependent Samples และการวิเคราะห์เนื้อหา ผลการวิจัย พบว่า 1) กิจกรรมประกอบไปด้วยแผนการจัดกิจกรรม จำนวน 5 เรื่อง ได้แก่ ปริมาณต่างๆ ของการเคลื่อนที่ การวัดอัตราเร็วของการเคลื่อนที่ในแนวตรง ความเร่ง ความสัมพันธ์ระหว่างกราฟความเร็ว เวลากับระยะทาง และสมการสำหรับคำนวณหาปริมาณต่างๆ มีความเหมาะสมอยู่ในระดับมาก (= 4.43, S.D. = 0.23) และมีดัชนีประสิทธิผลเท่ากับ 0.7674 2) ผลการใช้กิจกรรม พบว่า นักเรียนมีผลสัมฤทธิ์ทางการเรียนและความสามารถการแก้โจทย์ปัญหาหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญที่ระดับ .05 โดยนักเรียนสามารถกำหนดสัญลักษณ์แทนปริมาณทางฟิสิกส์ อธิบายหลักการทางฟิสิกส์ที่ใช้ในการแก้โจทย์ปัญหา วางแผนการแก้โจทย์ปัญหาและดำเนินการตามแผน อธิบายความสอดคล้องระหว่างผลลัพธ์และโจทย์ ตรวจคำตอบและอธิบายแนวทางที่จะใช้ในชีวิตประจำวันได้ คำสำคัญ: การแก้โจทย์ปัญหาทางฟิสิกส์  แนวคิดโรจาส์      The purposes of this research were: 1) to create a set of learning activities for solving physics problems based on Rojas Concept of Rectilinear Motion, verify the quality of the learning activities and establish the effectiveness index of the learning activities; 2) to compare students’ learning achievement and ability to solve physics problems before and after using those learning activities, and explore the ability of the students to solve physics problems qualitatively. The participants in this research were 39 Grade-10 students at Sukhothai Wittayakom School, selected by Cluster Random Sampling. The research instruments included the lesson plans, a physics learning achievement test, a test of the students’ physics problem solving ability, and a student behavior observation form. The data was analyzed by using a t-test for dependent samples and content analysis. The findings were as follows:      1. There were five lesson plans: (1) quantities of motion; (2) the speed measurement of rectilinear motion; (3) acceleration; (4) the relationship of speed, graph, time, and distance; and (5) equations for calculating quantities of motion. These lesson plans were considered appropriate at a high level (= 4.43, S.D. = 0.23), and the effectiveness index of the learning activities was 0.7674.      2. The learning achievement and ability of the students after using these learning activities were found to be higher than before using the learning activities. The difference was significant at p>.05. The students were able to write the physics symbols correctly, describe the principles and equations of physics in problem solving, plan a solution systematically, carry out the plan correctly and completely, explain the connection between the results and the problems, check the answers, and explain how to apply this knowledge gained these learning activities to use in their daily lives.   Keywords: Physics Problem Solving, The Concept of Rojas